Efficacy of Benson’s relaxation technique on stress and pain among patients undergoing maintenance hemodialysis: a systematic review - Abu Maloh, Haya Ibrahim Ali; Soh, Kim Lam; Chong, Seng Choi; Ismail, Siti Irma Fadhilah; Kim, Geok Soh; Abu Maloh, Dima Ibrahim; AbuRuz, Mohannad Eid (SAGE Publications, 2024)
Introduction: Stress and pain are high among patients undergoing hemodialysis. Benson’s Relaxation technique affected a wide range of physical and psychological signs and symptoms among patients undergoing hemodialysis. Objective: To evaluate the effectiveness of Benson’s Relaxation Technique in reducing stress and pain among patients undergoing maintenance hemodialysis. Materials and Methods: A systematic review of randomized controlled trials was conducted. A systematic literature search was carried out from 2000 to 2023. Searched databases included EBSCO-Host “Academic Search, Cochrane, CINAHL, Health Business, MEDLINE, Psychology and Behavioral Sciences, SPORTDiscus”, PubMed, Ovid, and Google Scholar. The Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines were conducted. RCTs were critically appraised using the Cochrane’s Risk of Bias Tool. Four RCTs met the inclusion criteria and included in this review since they were applicable to practice. Results: Four randomized controlled trials were identified supporting the use of Benson’s relaxation technique as a nursing treatment in managing stress and pain among patients undergoing maintenance hemodialysis, as it achieved a significant decrease in stress and pain scores. The overall quality of the randomized controlled trials was judged to be low to relatively moderate. Conclusions: Most of the randomized controlled trials lacked details on intervention adherence. It is recommended to conduct additional longitudinal randomized controlled trials in different countries with bigger sample sizes, to provide more evidence for generalizing outcomes.